2007
DOI: 10.1111/j.1439-0426.2007.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

A guide to the embryonic development of the shovelnose sturgeon (Scaphirhynchus platorynchus), reared at a constant temperature

Abstract: Described is the sequence and timing of embryologic development of shovelnose sturgeon, (Scaphirhynchus platorynchus) reared at a constant temperature 20 ± 0.5°C. Artificially spawned, fertilized eggs were held in a recirculating system. Embryos were sampled hourly during the first 48 h of development and every 3 h thereafter. Embryos were viewed and imaged at 35· magnification. The first cleavage furrow appeared 2 h post-fertilization; early (synchronous) cleavage was completed after 7 h. Blastulation conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Study endpoints focused on quantifying mortality and pathologies at early life stages. Life stages reported throughout are consistent with those previously described for shovelnose sturgeon . All studies were ended at 31 d postfertilization (dpf) to prevent mortality caused by starvation or other nontreatment‐related effects.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Study endpoints focused on quantifying mortality and pathologies at early life stages. Life stages reported throughout are consistent with those previously described for shovelnose sturgeon . All studies were ended at 31 d postfertilization (dpf) to prevent mortality caused by starvation or other nontreatment‐related effects.…”
Section: Methodsmentioning
confidence: 77%
“…Reduced hatchability in other fish species [30][31][32], including 2 species of Acipenser sturgeon [33], has been related to total PCB or TCDD exposure. Shovelnose sturgeon, and presumably pallid sturgeon, have larger posthatch yolk reserves than some lotic species [22]. Therefore, sequestering of dioxin-like PCBs and dioxin in the yolk may reduce expression of toxicity in pallid and shovelnose sturgeon during this early developmental phase.…”
Section: Discussionmentioning
confidence: 99%
“…For example, despite disparity in drift distance, both shovelnose and pallid sturgeon usually drifted in the lower 0.5 m of the water column (Braaten et al ., ). It has also been suggested that shovelnose sturgeon can be a model for pallid sturgeon as developmental patterns between these two species are similar during early life history (Colombo et al ., ). Additionally, others have shown that shovelnose sturgeon are adequate surrogates for studies regarding contaminants and contaminant uptake (Ruelle and Keenlyne, ; Schwarz et al ., ; Buckler, ).…”
Section: Discussionmentioning
confidence: 98%
“…These fish were estimated to be 13-14 years old based on the stocking history of the lake, their size relative to growth rates in the lake, and gonad development (Bruch et al 2001;Jackson et al 2002;Colombo et al 2007). From these fish, we collected gonad biopsies with the assistance of veterinarians from Cornell University (P. Bowser, N. Abou-Madi, and their coworkers).…”
Section: Rna Isolation and Cdna Library Constructionmentioning
confidence: 99%